Pengaruh Kombinasi Pupuk Organik Hayati dan Pupuk Anorganik Terhadap Pertumbuhan Vegetatif Jagung Manis (Zea mays L. saccharate Sturt ) Var. Panglima di Sumedang - Nugroho, Wisnu Aditya; Syafi'i, Muhammad; Rahayu, Yayu Sri; -, bahruzin (UNIVERSITAS LABUHANBATU, 2023)
Organic fertilizer made from medicinal plants and spices that have been fermented and mixed with favorable active microbes. The purpose of the study is to get a dose of biological organic fertilizer and inorganic fertilizer which gives the growth of sweet corn plants (Zea mays L. Saccharata Sturt) The highest commander variety. The study was conducted on the land owned by Biomethagreen (Educational House), Jl. Banjar Sari No.38, Awisurat Hamlet, Tanjungsari District, Sumedang Regency, West Java. The research method used is the experimental method, using a random design group (rack) a single factor consisting of 5 treatments and repeated 5 times, so there are 25 experimental units. The results showed that there was a concrete effect of the use of biological and inorganic organic fertilizer on plant height (1 and 3 MST), stem diameter (3, 5, 7, 9 MST), number of leaves (5 MST), anthesis silking intervals (ASI), and When a female flower appears in the growth of sweet corn plants (Zea mays L. Saccharata Sturt.) Panglima varieties. There is a combination of organic and inorganic fertilizer that produces the highest yield to the growth of sweet corn plants. The combination of treatment P1 (urea 250 kg/ha? NPK 300 kg/ha) affects the parameter of the stem diameter (1 and 5 MST), the number of leaves, interval silking anthesis (ASI), when male flowers appear, when appearing female flowers, combination of p4 effect on plant height parameters, and stem diameter (3, 7, 9 MST).Â Keywords : sweet corn, bio-organic fertilizers, inorganic fertilize, growth vegetativeÂ